John Stuart Mill and the Law of Markets - Balassa, Bela A. (Quarterly Journal of Economics, 1959)
I. Introduction, 263. — II. Walras' Law, Say's Identity, and Say's Equality, 264. — III. Mill's concepts of money, 265. — IV. Mill's interpretations of Say's Law and his dual concept of money, 267. — V. Mill's theory of crises, 269. — VI. Mill's views on general overproduction, 271. — VII. Conclusion, 273.